Farm mapping increases incomes for tea farmers [Uganda] - Koigi, Bob (Technical Centre for Agricultural and Rural Cooperation, 2018)
To ensure improved operations of a smallholder tea company in Uganda, and boost yields for farmers, an innovative garden geo-referencing project is working to gather local data.